Dialect atlas of north Yemen and adjacent areas - Behnstedt, P. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2016)
Since the author's publication of Die nordjemenitischen Dialekte. Teil 1: Atlas in 1985, a lot of new field work has been done in North Yemen and adjacent areas with new data especially from the extreme north of Yemen and neighbouring areas in Saudi Arabia. These are considered to be the most archaic Arabic dialect areas. The publication of a new atlas of the region in English therefore suggested itself. The atlas consists of 192 fully coloured maps with 30 phonetical and phonological maps, 100 morphological and 60 lexical ones. Depending on the subject the maps are accompanied by shorter or longer commentaries and paradigms. The book is of interest to Arabists, Semitists and dialectologists.